Teacher-Student Interpersonal Communication in Islamic Religious Education: Strengthening Learning Motivation in an Indonesian Public Junior Secondary School - Saputra, Danang; Hasirah (Universitas Islam Negeri Raden Intan Lampung, 2026)
This qualitative descriptive case study examines how an Islamic Religious Education (IRE) teacher used interpersonal communication to strengthen students' learning motivation in Class VIII B at Public Junior Secondary School (SMPN) 44 Tebo Regency, Jambi Province, Indonesia. Data were generated through classroom observation, semi-structured interviews, and documentation involving one IRE teacher, five interviewed students from a class of 32 students, and school-level informants. The data were analyzed through data reduction, data display, and conclusion drawing, with source, method, and time triangulation used to support trustworthiness. The findings show that teacher-student interpersonal communication strengthened learning motivation through five interconnected strategies: openness in inviting questions and opinions, empathy toward students' learning difficulties, supportive communication through praise and encouragement, positive classroom attitudes, and equality in giving students opportunities to participate. These strategies created a safer and more dialogic classroom climate, increased students' confidence to ask questions, and encouraged participation in Islamic Religious Education learning. The study contributes a contextual IRE communication-motivation model that links dialogic interaction, relational care, and inclusive participation as practical pathways for improving student motivation in public junior secondary education.